PENGARUH PROFITABILITAS, LIKUIDITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR PERBANKAN - NITA, EVARYANTI KARIMUN; Simanjuntak, Jontro (LPPM Universitas Putera Batam, 2021)
The purpose of this study was to determine the effect of profitability (ROA), liquidity (LDR) and company growth on the value of the banking sector companies listed on the Indonesia Stock Exchange (BEI). The population in this research have 45 banking companies and the sample selected according to the criteria was 24 banking companies with using purposive sampling method. The data source used is secondary data and the type of data is quantitative data. Banking company financial report data used in the period 2015-2019. The analysis method used is multiple linear regression, t test, f test and analysis coefficient of determinant (R2) by using SPSS version 25. The results of the research showed that profitability (ROA) and liquidity (LDR) have a positive and significant effect on firm value. Meanwhile, company growth has a positive and insignificant effect. And simultaneously profitability (ROA), liquidity (LDR) and company growth have a positive and significant effect on the value of the banking sector companies listed on the Indonesia Stock Exchange for the period 2015-2019.